A European niche strategy in the global chips war - Daniel Gros (EconPol Forum, 2026)
The semiconductor industry comprises two distinct sectors: advanced chips for smartphones or data centers and less advanced ones for cars. While political and media attention focuses on advanced chips, European industry does not use them. NVIDIA and TSMC dominate the supply of the most advanced chips, but EU firm ASML is the sole supplier of the machinery needed for these chips. The EU Chips Act finances legacy node chips, which are needed by the European industry but represent a medium-tech sector with low profit margins. The EU should focus its support on its comparative advantage - machines for chip production - rather than on capital-intensive fabs for legacy chips.
Keywords: 330